Identification of GPR35-associated metabolic characteristics through LC-MS/MS-based metabolomics and lipidomics - Qiqing Zhang; Xian Zhao; Siyuan Qin; Qinwen Xiao; Yuan Tian; Zunjian Zhang; Pei Zhang; Fengguo Xu (Acta Materia Medica, 2024)
G protein-coupled receptor 35 (GPR35) has gained increasing attention as a promising target in treating inflammatory and gastrointestinal tract conditions, cardiovascular diseases, and cancer. Metabolites including kynurenic acid, lysophosphatidic acids, chemokine 17, and 5-hydroxyindole acetic acid have been suggested to be endogenous ligands of GPR35. However, little is known regarding the downstream metabolic characteristics upon GPR35 regulation. Herein, four GPR35 interventions in cell models, comprising GPR35 knock-down, over-expression, activation, or inhibition, were established through lentiviral transduction, or the use of a potent agonist (pamoic acid) or antagonist (ML194). Targeted metabolomics and pseudotargeted lipidomics were performed on these cell models to capture GPR35-associated metabolites and lipids. Levels of 75 metabolites and 204 lipids were significantly altered in response to one or more GPR35 interventions. Levels of metabolites involved in fatty acid β-oxidation and phosphatidylethanolamine metabolism were notably altered. This study reports the first exploration of the metabolic characteristics of GPR35, and may aid in understanding of the potential mechanisms and functions of GPR35 in various physiological and pathological conditions.